FINANCIAL RISK AS MEDIATION OF THE EFFECT OF PERCEIVED QUALITY AND PERCEIVED SACRIFICE ON PERCEIVED VALUE FOR CUSTOMERS RESTAURANT PADANG - Alfattory Rheza Syahrul; Syailendra Eka Saputra; Neffi Sulkaisi; Nora Susanti (JURNAL ECONOMICA : Research of Economic And Economic Education, 2026)
Using financial risk as a mediating variable, this study attempts to demonstrate and examine how perceived quality and perceived cost affect perceived value. Customers who frequent Padang restaurants make up the sample for this study. Respondents who fulfilled the conditions were given questionnaires in order to collect data. The Smart PLS application is used to process the path analysis analysis approach. There were 210 Padang restaurant patrons among the total replies. This study examines individual intentions using the Theory of Planned Behavior (TPB), emphasizing the connection between subjective norms, intentions, and individual attitudes. The outcomes attained include The perceived value of the food offered at restaurants Padang is positively impacted by perceived quality, while the perceived value of patrons who dine at Padang restaurants is negatively impacted by perceived sacrifice. Perceived sacrifice has a positive and significant impact on perceived value through financial risk as a mediating variable for patrons of Padang restaurants, while perceived quality has no discernible effect on perceived value. Financial risk also has a positive effect on consumers' perceptions of the value of dining at restaurants Padang